The Effect Of Current Ratio (CR), Return On Asset (Roa) And Debt To Equity Ratio (Der) On Stock Prices With Dividend Policy As An Intervening Variable - Yohannes Ivan Prabowo (Publikasi Indonesia, 2023)
This study examines the effect of the Current Ratio, Return on Assets, and Debt to Equity Ratio on Stock Prices with Individual Policy as an Intervening variable. The population of this study is manufacturing companies listed on the IDX for the period 2016-2022. Samples are selected through purposive sampling. Data processing techniques use multiple regression analysis. The results showed that the current ratio, return on assets, and debt-to-equity ratio have a significant positive influence on stock prices with dividend policy as an intervening variable